2015
DOI: 10.1111/jcpp.12457
|View full text |Cite
|
Sign up to set email alerts
|

Methylomic analysis of salivary DNA in childhood ADHD identifies altered DNA methylation in VIPR2

Abstract: Background Peripheral epigenetic marks hold promise for understanding psychiatric illness and may represent fingerprints of gene–environment interactions. We conducted an initial examination of CpG methylation variation in children with or without attention-deficit/hyperactivity disorder (ADHD). Methods Children age 7–12 were recruited, screened, evaluated and assigned to ADHD or non-ADHD groups by defined research criteria. Two independent age-matched samples were examined, a discovery set (n = 92, all boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 67 publications
6
106
4
Order By: Relevance
“…Conversely, our findings regarding peroxisomal processes lend support to the involvement of mechanisms related to fatty acid oxidation in ADHD, as previously reported by Wilmot et al21 Peroxisomes are cell components that play a key role in the metabolism of essential fatty acids from the omega-3 family. In particular, dietary alpha-linolenic acids are transformed into docosahexaenoic acid (DHA) through a final β-oxidation reaction that takes place in the peroxisomes 40.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, our findings regarding peroxisomal processes lend support to the involvement of mechanisms related to fatty acid oxidation in ADHD, as previously reported by Wilmot et al21 Peroxisomes are cell components that play a key role in the metabolism of essential fatty acids from the omega-3 family. In particular, dietary alpha-linolenic acids are transformed into docosahexaenoic acid (DHA) through a final β-oxidation reaction that takes place in the peroxisomes 40.…”
Section: Discussionsupporting
confidence: 91%
“…With regard to contrasting results, we found no evidence of differential methylation in VIPR2 (a gene linked to mood disorders and circadian rhythm regulation), which was identified as a top hit by the only other published methylome-wide study on ADHD 21. We also found no evidence of differential methylation in DRD4 , which was reported as significantly associated with ADHD in two previous candidate gene studies 18,19.…”
Section: Discussioncontrasting
confidence: 77%
“…A GWA analysis in 1,000 participants found that the vasoactive intestinal peptide (VIP) pathway was strongly associated with fat mass and with BMI, suggesting that the VIP pathway may play an important role in the development of obesity (48). In a study using the 450k array, lower VIPR2 methylation was found in the saliva of children with attention deficit hyperactivity disorder (ADHD), relative to controls (49), albeit at different sites than those identified in the present study. Given previously identified associations between maternal BMI and offspring ADHD (50)(51)(52)(53), further work is warranted to explore the extent to which VIPR2 gene function (driven either by genetic variation or regulation by methylation) might explain associations between maternal adiposity and neurodevelopment of the offspring.…”
Section: Discussioncontrasting
confidence: 49%
“…Forty-two sites were on this list: seven located in regions containing SNPs, 11 in regions containing repeat sequences and four in regions where insertions or deletions are found. These [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Additionally, all cohortspecific analyses were conducted using robust linear regression, which is designed to be robust to outliers in the outcome variable (methylation).…”
Section: à7mentioning
confidence: 99%
“…After filtering genes based on statistical and biological criteria, Wilmot et al. () found that DNAm of the neuropeptide receptor gene VIPR2 in saliva was lower in the ADHD group versus controls (all boys), and this association was confirmed in an independent sample of age‐matched children. At a broader level, genes that were nominally associated with ADHD were found to be enriched for biological processes related to inflammation and monoamine neurotransmission.…”
Section: Dnam and Child Psychopathology: The B Pathmentioning
confidence: 98%